Development of Railways in New Marketing Conditions - Blašković Zavada, Jasna; Zavada, Josip; Hozjan, Dubravka (Promet - Traffic&Transportation, 2007)
As a traffic system, railway is experiencing possibly the biggestorganizational and systemic changes ever, in its long existence.It has always been under the patronage of the state. It hashad privileged position on the transport market, and its losseswere covered by the state. In comparing the railways as a publictransport system and other transport systems, especially theroad system, railways features significant innate advantageswhich should be used by stimulating traffic policy. This paperstudies the future development of the railway from the transportaspect in the new conditions of the transport market, marketliberalization on railway lines and the privatization process ofthe railway as transport service provider. It presents the basiccharacteristics of the railway which emphasise its advantagesand drawbacks compared to other traffic systems. The characteristicsof the transport market are presented, and the positionof the railway in the given circumstances is analysed. The paperalso analyses the political relation of the governments of somecountries and EU towards traffic and favouring of individualsystems.